Macromol. Rapid Commun. 9/2016. Issue 9 (2nd May 2016) - Xie, Lan; Xu, Huan; Li, Zhong‐Ming; Hakkarainen, Minna
Abstract : Back Cover: The shish‐kebab superstructure of poly(lactic acid) stereocomplex was developed in a transient and strong shear flow. The shear‐aligned stereocomplex chains were preferentially assembled into the central shish, while the crystal form of the lateral kebabs showed strong dependency on the crystallization temperature. Further details can be found in the article by L. Xie, H. Xu, Z.‐M. Li, and M. Hakkarainen* on page 745.